History and Theology in the Gospels: Seventh International East-West Symposium of New Testament Scholars, Moscow, September 26 to October 1, 2016 - Nicklas, Tobias; Niebuhr, Karl-Wilhelm; Seleznëv, Michail; König, Judith; Draughon, Rebecca (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
Der vorliegende Band enthält die Beiträge zum siebten internationalen Ost-West-Symposium neutestamentlicher Wissenschaftler, das 2016 in Moskau stattfand. Die Beiträge bieten orthodoxe, protestantische und katholische Perspektiven auf die Frage nach dem Verhältnis von Geschichte und Theologie in den Evangelien.InhaltsübersichtI. Opening Paper and Plenary Discussion Metropolitan Hilarion: The »Demythologization« of New Testament Studies (Opening Paper) – Carl R. Holladay: The Session in Retrospect: Plenary Discussion – William Loader/Francis Watson/Joel Marcus: Responses – Metropolitan Hilarion: Counter Response II. Main Papers Joel Marcus: History and Theology in Matthew – Vladan Tatalović: The Matthean Passion Narrative in Serbian Interpretation – Francis Watson: History and Theology in Mark – Cosmin Pricop: Between Criticism and Patristics: The Transfiguration Story in Mark from an Eastern Point of View – Carl R. Holladay: The Lukan Travel Narrative: History and Theology in Luke's Gospel – David P. Moessner: The Problem of the Continuity of Acts with Luke, the Church's Reception of Two Separated Volumes, and the Construction of Luke's 'Theology': Toward a Theology of Jesus the »Christ« of Israel and the »Lord of All« in the Light of the Worldwide Church (ἡ ἐκκλησία) of Luke's 'Gospel Acts' – Margareta Gruber: »… but he was acting in the temple of his body«: Symbolic Performance of Death and Resurrection in the Cleansing of the Temple (John 2:13–23) – Anatoly A. Alexeev: The Gospel of John: From Christology to Theology – Armand Puig i Tàrrech: The Figure of Jesus According to the Canonical Gospels – Stefanos Alexopoulos: The Gospel Narrative in Byzantine Liturgy – Tobias Nicklas: History and Theology in the Non-Canonical Gospels III. Seminar Papers Ekaterina Matusova: A New Translation of Ps 78:2 (77:2 LXX) in Matt 13:35 – Lauri Thurén: The Final Countdown: The Last Judgment in the Light of Narratology and Argumentation Analysis – Petr Mareček: The Function and Importance of Matthew 28:16–20 in the Gospel of Matthew – Manuel Vogel: Matthew's Post-War Mission to Israel: Some Observations on a Jewish Reading of the First Gospel – Christos Karakolis: Is There Such a Thing as Prophetic Christology in the Gospel of Mark? A Reader-Centered Approach – Stelian Tofană: Jesus' Portrait in the Gospel of Mark Reflected in Two Christological Titles: Son of Man and Son of God – Alexey Somov: Jesus' Banquet Etiquette (Luke 14:7–14) and the Heavenly Banquet – Thomas Schumacher: The Lukan Assumption Stories (Luke 24:50–53; Acts 1:9–11): Their Narrative Function and Theological Relevance within the Lukan Corpus – Andrei S. Desnitsky: Translating Luke between Narrative and Theology – Hans-Ulrich Weidemann: From Cana to Cana, from Jews to Gentiles? Observations on the Johannine Cana-Cycle (John 2–4) – James Buchanan Wallace: Of Manna and Eucharist: The Feeding of the Five Thousand in the Gospel of John – Petr Shitikov: Cognitive Approach to John – Maria Karyakina: οὐχ ἁρπαγμὸν ἡγήσατο τὸ εἶναι ἴσα θεῷ: To the Question of the Meaning of Philippians 2:6b – Hieromonk Justin: 'For Moses Wrote of Me': Reflections from Having Lived at Mount Sinai